Seeing Differently, Seeing Anew - Leila Hall (The Thinker)
ith a focus on two recent queer-themed short stories from Kenya and South Africa, this article considers how the use of a child focaliser in fictional representations of early experiences of same-sex desire can disrupt and subvert ideals of childhood ‘innocence’ and the problematic conflation of paedophilia with same-sex sexuality. The two stories discussed in this article – Idza Luhumyo’s “Nine Pieces of Desire” (2017) and Kharys Laue’s “Plums” (2018) – importantly narrate childhood experiences of same-sex sexuality that are not associated with paedophilia or sexual abuse, but that rather focus on young protagonists’ experiences of the restrictiveness and violence associated with hetero-patriarchal norms. The article argues that the stories eschew the simplistic binary of innocent children/perverse homosexuals in two important ways. Firstly, the stories re-frame the notion of same-sex sexuality itself as ‘perverse’ and violent by instead locating violence and repression within the hetero-patriarchal norms that are ostensibly meant to protect children from harm. Secondly, through the use of complex characterisation and the unabashed depiction of childhood sexuality, the stories implicitly challenge the ideal of childhood ‘innocence’: an ideal which is central to discourses and constructs that diametrically oppose ‘innocent children’ with ‘perverse homosexuals’. The article also explores how the use of a child’s perspective can help us to see socially constructed adult norms ‘anew’. In contrast with the delimitations and divisiveness of heteropatriarchy and its interconnected systems of power, the stories’ young focalisers represent instinct, defiance, and relationality: qualities and alternative points of view that could have wider implications for debates surrounding same-sex sexualities in contemporary African contexts.